Enterprise-focused management changing the face of project management : the application of the theory of constraints to the enterprise management of companies - Hutchin, Ted (Thomas Telford, 2001)
This title represents a new voice in the drive for enterprise thinking within organisations. Although enterprise resource planning and similar approaches are now commonplace in industry, they continue to deliver disappointing results. This title will enable companies to turn their investment into bottom-line improvement.